1993
DOI: 10.2169/internalmedicine.32.607
|View full text |Cite
|
Sign up to set email alerts
|

Response to Octreotide of Intestinal Pseudoobstruction and Pneumatosis Cystoides Intestinalis Associated with Progressive Systemic Sclerosis.

Abstract: Intestinal pseudoobstruction and pneumatosis cystoides intestinalis are uncommon complications of progressive systemic sclerosis. Wereport a 26-year-old womanwith this disorder who responded poorly to conventional treatment. Subcutaneous administration of octreotide, a longacting somatostatin analogue, at a dose of50 J^g/day for 3 weeks, relieved symptoms such as nausea and bloating. There was also a markeddecrease of intestinal gas accumulation, as documentedon X-ray films. (Internal Medicine 32: 607-609, 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…The possible rationale of oxygen use suggests that increased oxygen content in the gas cysts will raise the diffusion gradient between cysts and venous capillary flow and enhance their absorption 30 . The effectiveness of octreotide was demonstrated in SSc patients with PCI resistant to other treatments (case 3) 7 . In SSc patients with known macrovascular disease, angioplasty and stent insertion failed; PCI resolved only after initiation of broad‐spectrum intravenous antibiotics and parenteral nutrition 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The possible rationale of oxygen use suggests that increased oxygen content in the gas cysts will raise the diffusion gradient between cysts and venous capillary flow and enhance their absorption 30 . The effectiveness of octreotide was demonstrated in SSc patients with PCI resistant to other treatments (case 3) 7 . In SSc patients with known macrovascular disease, angioplasty and stent insertion failed; PCI resolved only after initiation of broad‐spectrum intravenous antibiotics and parenteral nutrition 5 .…”
Section: Discussionmentioning
confidence: 99%
“…We found 110 patients treated conservatively by different modalities; in 98 patients (89%) PI resolved while 11 patients (11%) died. Table 1 summarizes conservative treatment in PI [5, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…Several authors described good response and resolution of pseudoobstruction with the use of octreotide [12, 19, 20, 21]. Kobayashi et al [12] reported a 26-year-old woman with PI who responded poorly to conventional treatment. Subcutaneous administration of octreotide, at a dose of 50 μg/day for 3 weeks, relieved symptoms such as nausea and bloating.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate after all these types of treatment within 18 months is 30-40 percent [8]. Successful treatments with infliximab and octreotide are also reported in patients with connective tissue diseases [64][65].…”
Section: Antibioticsmentioning
confidence: 99%